Small and Medium enterprises in the Kingdom of Saudi Arabia between Reality and Hope, according to 2030 Vision: An Empirical Study - Mansour, Ali Nageh Ali (Journal of Economic, Administrative and Legal Sciences, 2020)
The aim of this research is to analyze the most important obstacles and challenges facing small and medium enterprises within the Kingdom of Saudi Arabia in the light of international experiences, and to analyze and evaluate the role of the Small and Medium Enterprises Authority “Monshaat” in facing challenges facing small and medium enterprises inside the Kingdom; and to know the true reality of small and medium enterprises in The Kingdom of Saudi Arabia as well as reaching the hoped- for according to 2030 Vision, which aims to reform the Saudi economy and continue its growth and end its dependence on oil as a main source of income.The researcher analyzed the current situation of small and medium enterprises in the Kingdom of Saudi Arabia and compared them to the global situation through studying and analyzing leading global experiences and identifying aspects of benefiting from them.The research relied on the deductive approach, which is the approach that begins with the theory and ends with its applicability to the ground. The research also used the descriptive approach to describe the topic of the research, its importance, goals, and the most important studies that dealt with the role of small projects in economic development both inside and outside the Kingdom. The comparative approach to making comparisons from and reviewing the experiences of other countries and extracting lessons learned from them. It also relied on the standard method, which aims to measure economic phenomena and variables.This research found that there are many difficulties that hinder these projects from achieving the goals of the vision, including obtaining financing, as the rate of financing small enterprises does not exceed 5% of the total financing in the Kingdom. It is a small percentage compared to international rates. The result is a decrease in the contribution of small and medium enterprises to the gross domestic product if they do not exceed 20% and 53% of jobs in the Kingdom of Saudi Arabia. The Kingdom's Vision 2030 aims to raise this percentage to 35% by 2030, and this percentage reaches about 70% in developed countries, The number of small enterprises reached 12% of the number of projects for the year 2018, and it contributes about 29% of the total revenues of enterprises, according to the data for the second quarter of 2016.The researcher recommends decision- makers and those who are interested in business leaders inside the Kingdom to overcome the challenges facing small projects and entrepreneurs by providing them with adequate support, whether material or logistical support or both together, and work to establish a financial fund to finance small and medium projects with low benefits, and share the fund with proportions Certain of the annual profits during a specific period, depending on the value of the loan, the size of the facility, the value of revenue, the idea of ​​the project, and converting the Public Authority for Small and Medium Enterprises in the Kingdom into an independent ministry whose mission is to take great care of small projects and For medium.
Keywords: small and medium enterprises; sustainable development; Saudi Vision 2030; entrepreneurship